(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
In this article methods of planning, and organization of independent work and evaluation of educational results in the teaching of chemistry in the credit module system have been learnt and converted student’s midterm scores into credit scores also analyzed.